When tradition becomes expression: The transformation of interpretative frameworks of Balinese traditional architecture in a global Airport (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This study examines the transformation of Balinese Traditional Architecture (BTA) in public buildings operating within the context of global architecture, using I Gusti Ngurah Rai International Airport as a case study. The application of traditional architectural elements in contemporary buildings is often understood as an effort to express local identity; however, such approaches generally remain at the level of visual and symbolic representation, without further investigating the more fundamental shifts in architectural meaning that occur. This research adopts a qualitative, analytic–interpretative approach by formulating a framework for reading the transformation of expression through four interrelated mechanisms: reduction, rescaling, rematerialization, and recontextualization. These four mechanisms are not positioned as design techniques, but rather as conceptual tools for understanding how architectural meaning changes when Balinese Traditional Architecture is displaced from its original context. Initially rooted in spatial systems, ritual practices, and cosmological principles, it is transformed as it enters global infrastructure characterized by different functional requirements, scales, and technological demands. The findings indicate that the expression of BTA in airport buildings does not function as a continuation of its traditional spatial system and meanings. The Domestic Terminal tends to emphasize reduction and rematerialization, while the International Terminal demonstrates a stronger intensity of rescaling and recontextualization. Traditional architectural elements undergo a systematic transformation, shifting from functional and symbolic components within a system of dwelling into representational devices that construct territorial identity and visual recognition. This transformation signifies a change in the ontological status of BTA, from architecture as a system of habitation to architecture as a language of expression. By positioning this transformation as an epistemic process, the study contributes to the development of a conceptual framework for understanding vernacular architecture within contemporary public buildings. The findings further provide broader theoretical implications for examining the relationship between tradition, modernity, and architectural meaning in the context of globalization.
Keywords: Architectural expression; Balinese traditional architecture; Global airport; Transformation of interpretative frameworks; Vernacular architecture